2006
DOI: 10.1007/s00436-006-0287-8
|View full text |Cite
|
Sign up to set email alerts
|

No variation in the prevalence of point mutations in the Pfcrt and Pfmdr1 genes in isolates from Gabonese patients with uncomplicated or severe Plasmodium falciparum malaria

Abstract: In Lambaréné (Gabon), where a high level of Plasmodium falciparum resistance to chloroquine has been reported, we assessed the relationship between polymorphisms in the P. falciparum chloroquine resistance transporter (Pfcrt) and multidrug resistance-1 (Pfmdr1) genes and the clinical severity of malaria. Ninety-one and 60 P. falciparum isolates from children with uncomplicated or severe malaria were collected in 1996 and 2002, respectively. Single nucleotide mutations at codon 76 in the Pfcrt gene and at codon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…We first tried to determine by qPCR the alleles present at two genes involved in chloroquine resistance: pfcrt and pfmdr1. In Gabon, the prevalence of the two point mutations conferring resistance (pfrct 76T and pfmdr1 86Y) in human P. falciparum populations is high (>85%) (15,16). Hence, we hypothesized that if the MO454 The tree was constructed by using maximum likelihood methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tried to determine by qPCR the alleles present at two genes involved in chloroquine resistance: pfcrt and pfmdr1. In Gabon, the prevalence of the two point mutations conferring resistance (pfrct 76T and pfmdr1 86Y) in human P. falciparum populations is high (>85%) (15,16). Hence, we hypothesized that if the MO454 The tree was constructed by using maximum likelihood methods.…”
Section: Resultsmentioning
confidence: 99%
“…For pfcrt, the MO454 isolate (note that Plasmodium blood stages are haploid) displayed the wild allele at codon 76 (pfcrt K76). This allele is absent in the human P. falciparum population in Lambaréné (Moyen Ogooué province), a city <30 km away from the village where MO454 was collected (16) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, Giha and collaborators found in Sudan that the lethal malaria form was rather associated with the wild type PfCRT K76 although the difference in the frequency of the chloroquine resistant parasites in patients suffering from severe malaria and from non-severe malaria was not significant [7]. Similarly, in a more recent study in Congo, Mayengue and collaborators did not find any relation between the severity of the disease and the presence of the mutant allele PfCRT 76T [13]. We note that in the Sudanese study, the sample size (n = 47) was rather small and not sufficient to support the hypothesis of increased virulence of chloroquine sensitive strain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from India [11] and Mali [12], but not Sudan [13] or Gabon [14], showed associations between presence of the pfcrt 76T mutation and severe malaria, but these associations may have been due to clinical progression after chloroquine treatment failure, rather than variations in parasite virulence. Previously, differences in genotypes between parasites causing symptomatic and asymptomatic infections were studied in samples from a cross-sectional study of children from Tororo, Uganda.…”
Section: Introductionmentioning
confidence: 99%